2014
DOI: 10.1051/0004-6361/201220367
|View full text |Cite
|
Sign up to set email alerts
|

3D global simulations of a cosmic-ray-driven dynamo in dwarf galaxies

Abstract: Context. Star-forming dwarf galaxies can be seen as the local proxies of the high-redshift building blocks of more massive galaxies according to the current paradigm of the hierarchical galaxy formation. They are low-mass objects, and therefore their rotation speed is very low. Several galaxies are observed to show quite strong magnetic fields. These cases of strong ordered magnetic fields seem to correlate with a high, but not extremely high, star formation rate. Aims. We investigate whether these magnetic fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 38 publications
4
20
0
Order By: Relevance
“…We note that our results are broadly consistent with studies of cosmic ray driven dynamos (e.g. Siejkowski et al 2014, and references therein). These studies find that for, modest values of the SFR, galactic fields are enhanced, but that the dynamo ceases to operate for very high values of SFR.…”
Section: Discussionsupporting
confidence: 92%
“…We note that our results are broadly consistent with studies of cosmic ray driven dynamos (e.g. Siejkowski et al 2014, and references therein). These studies find that for, modest values of the SFR, galactic fields are enhanced, but that the dynamo ceases to operate for very high values of SFR.…”
Section: Discussionsupporting
confidence: 92%
“…One should have in mind the existence of a feedback effect of supernova and superbubbles on the global galactic ecology. This is the effect of large scale galactic magnetic field amplification by the cosmic-ray-driven dynamo on the timescale of about 150 Myr simulated by Hanasz et al (2009), Siejkowski et al (2014). Price and Bate (2008) demonstrated that even a very low magnetic field is able to significantly influence the star formation process.…”
Section: Hydrodynamical Models Of Massive Star Winds and Superbubblesmentioning
confidence: 93%
“…In this prescription, supernova events occur in proportion to star formation activity, and provide localized injections of thermal energy, metal-rich material, and a low level of toroidal magnetic field. This is in contrast to a number of earlier studies in which supernovae were assumed to function strictly as sources of energetic cosmic rays (Hanasz et al 2009;Siejkowski et al 2014;Kulpa-Dybeł et al 2011. In this study, we will neglect the influence of cosmic rays, and focus on the role of turbulence driven by supernovae through their thermal feedback.…”
Section: Introductionmentioning
confidence: 93%
“…In their approach, only 10% of supernova events included a magnetic field. The same approach was adopted in Kulpa-Dybeł et al (2011 to simulate dynamo activity in barred spiral galaxies, and by Siejkowski et al (2014) to study dwarf galaxies. Beck et al (2013) also utilized a magnetic dipole configuration as supernova source terms.…”
Section: Comparison With Other Computational Approachesmentioning
confidence: 99%